Comparative Evaluation of Electrostatic Sprayer for Cotton Crop - Patel, Bharat; Singh, Manjeet; Mishra, P. K.; Manes, G. S.; Sharma, Karun; Mishra, Abhinab (International Journal of Bio-resource and Stress Management, 2016)
A comparative evaluation of an electrostatic sprayer (make ESS) was conducted at Krishi VigyanKendra, Faridkot, Punjab, India. Effect of electrostatic spraying on droplet density, area coverage, spray deposition, uniformity coefficient, droplet size and bio-efficacy were observed and comparison was made between different types of sprayer i.e. electrostatic sprayer, lever operated knapsack sprayer, power operated knapsack sprayer and tractor operated gun type sprayer. It was found that on an average droplet density by electrostatic sprayer was significantly (p=0.0000017) 47.19, 68.07 and 78.26% higher than that of TOG, POK and LOK sprayers respectively. It was found that maximum number of droplets, for electrostatic sprayer was 42 at 48.61 μ, for POK sprayer 10 at 98.68 μ, for LOK sprayer 11 at 98.68 μ and TOG sprayer 12 at 125.00 μ. Percentage area covered by droplets on average over the plant (top, middle and bottom leaves of plant) was significantly (p=0.012) 34.69, 24.42 and 69.25% higher than of POK sprayer, LOK sprayer and TOG sprayer respectively. The volume of spray deposition on leaves was significantly (p=0.022) 50.20, 44.42 and 62.63% lesser than TOG, POK and LOK respectively. On an average bio-efficacy of electrostatic sprayer was more (47.75, 59.47 and 26.57%) than other three sprayers viz. POK, LOK and TOG sprayers respectively.